2009
DOI: 10.1186/1471-2407-9-441
|View full text |Cite
|
Sign up to set email alerts
|

Transcribed-ultra conserved region expression is associated with outcome in high-risk neuroblastoma

Abstract: BackgroundNeuroblastoma is the most common, pediatric, extra-cranial, malignant solid tumor. Despite multimodal therapeutic protocols, outcome for children with a high-risk clinical phenotype remains poor, with long-term survival still less than 40%. Hereby, we evaluated the potential of non-coding RNA expression to predict outcome in high-risk, stage 4 neuroblastoma.MethodsWe analyzed expression of 481 Ultra Conserved Regions (UCRs) by reverse transcription-quantitative real-time PCR and of 723 microRNAs by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 29 publications
2
94
1
Order By: Relevance
“…Previous research has shown that miR-9 upregulation correlates with breast cancer metastasis (Ma et al, 2010), supporting our finding of miR-9 as a new biomarker for advanced neuroblastoma. Furthermore, we also found miR-9 to be significantly upregulated in short-term survival patients within the advanced stage neuroblastoma group in other publicly available data (Scaruffi et al, 2009), confirming the validity of our finding. To increase the specificity of differentiating high-risk and short-term survival groups, further research is needed to identify additional miR-9 activating factors besides MYCN as well as the common biological pathways of miR-9 target genes in neuroblasts (Fig.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Previous research has shown that miR-9 upregulation correlates with breast cancer metastasis (Ma et al, 2010), supporting our finding of miR-9 as a new biomarker for advanced neuroblastoma. Furthermore, we also found miR-9 to be significantly upregulated in short-term survival patients within the advanced stage neuroblastoma group in other publicly available data (Scaruffi et al, 2009), confirming the validity of our finding. To increase the specificity of differentiating high-risk and short-term survival groups, further research is needed to identify additional miR-9 activating factors besides MYCN as well as the common biological pathways of miR-9 target genes in neuroblasts (Fig.…”
supporting
confidence: 90%
“…Scaruffi et al published research on non-coding RNA expressions with regard to outcome in high-risk neuroblastoma (Scaruffi et al, 2009). Among 31 high-risk, stage 4 neuroblastoma samples, miRNA expressions came from 17 short-term survivors (dead within 36 months from diagnosis) and 14 long-term survivors (alive with an overall survival time > 36 months) were deposited in GEO (Series accession number GSE16444).…”
Section: Mir-9 Signature In Short -And Long -Lived Patientsmentioning
confidence: 99%
“…TUCRs are widely expressed in neuroblastoma, and a signature based on the expression of 28 T-UCRs has been shown to be associated with good outcome in noninfant patients with metastatic disease (84). Furthermore, Mestdagh and colleagues (85) investigated the global T-UCR expression in neuroblastoma and found a signature of 7 T-UCRs significantly upregulated in MYCN-amplified tumors (n ¼ 18) compared with nonamplified tumors (n ¼ 31).…”
Section: N-myc Alters Expression Of Other Noncoding Rnasmentioning
confidence: 99%
“…Scaruffi et al [48] suggested that deregulation of the microRNA/T-UCR network may play an important role in the pathogenesis of neuroblastoma and tumor-associated T-UCRs in CLL were found to be regulated by certain miRNAs [47]. These results led to the hypothesis that T-UCRs along with miRNAs may define signatures associated with the diagnosis, prognosis and treatment of tumors.…”
Section: Transcribed Ultraconserved Regions (T-ucrs)mentioning
confidence: 99%